Costing curative outpatient care for the poorest in Burkina Faso: informing universal health coverage and leaving no one behind - Yvonne Beaugé; Valéry Ridde; Sidibé Souleymane; Joël Arthur Kiendrébéogo; Hoa Thi Nguyen; Emmanuel Bonnet; Manuela De Allegri (BMC Health Services Research)
Abstract Introduction The poorest in Burkina Faso face numerous barriers to healthcare access, including financial and geographic obstacles, as well as a high burden of chronic conditions and multimorbidity. This study estimates the average cost of providing curative outpatient consultations at first-level healthcare facilities to the poorest in Burkina Faso. It also estimates the budgetary impact of scaling up free access to these services nationwide. The findings provide essential evidence on cost structures to inform decision-makers in developing policies aimed at achieving universal health coverage and ensuring that no one is left behind. Methods We conducted a micro-costing study to estimate the economic costs of providing curative outpatient healthcare services to the poorest at first-level healthcare facilities, considering a health system perspective. We measured the consumption of capital costs (building and equipment) using survey data from 32 primary health facilities and recurrent costs (drugs and consumables) from medical records of 1380 poor patients in Diébougou district. These individuals were targeted and exempted from user fees through a community-based targeting approach. We obtained unit costs from official price lists, pharmacy registries, and expert interviews. We calculated the national budget for providing curative care services to the exempted poorest based on the average cost per first-level consultation. Results The estimated capital and recurrent costs of providing curative care services ranged between USD 0.59 - USD 0.61 and USD 2.58 - USD 5.00, respectively. The total cost ranged between USD 3.17 - USD 5.61 per first-level consultation. Providing curative care to the bottom 20% of the population, assuming 0.25 healthcare contacts per person per year, would result in an annual expense ranging from USD 2.77 M to USD 5.38 M (0.74-1.43% of the healthcare budget in 2019). With 2 healthcare contacts per person per year, costs increase to USD 22.19 M to USD 43.05 M (5.91-11.45% of the healthcare budget). Conclusion The results can inform policies aimed at expanding access to curative care for the poorest in Burkina Faso, contributing to the goals of universal health coverage and leaving no one behind. Further research is needed to enhance cost estimation and budgeting for higher-level care in the country.